2007
DOI: 10.1534/genetics.107.070862
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Epigenetic Regulation, ORC Binding and Developmental Timing of DNA Replication Origins in the Genus Drosophila

Abstract: There is much interest in how DNA replication origins are regulated so that the genome is completely duplicated each cell division cycle and in how the division of cells is spatially and temporally integrated with development. In the Drosophila melanogaster ovary, the cell cycle of somatic follicle cells is modified at precise times in oogenesis. Follicle cells first proliferate via a canonical mitotic division cycle and then enter an endocycle, resulting in their polyploidization. They subsequently enter a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Moreover, in higher eukaryotes, early replication correlates with a high probability of transcription and the presence of histone modifications characteristic of active chromatin such as histone acetylation (Schwaiger et al 2009;Hansen et al 2010). Histone hyperacetylation has been directly implicated to facilitate origin activation and thereby early replication timing (Aggarwal and Calvi 2004;Calvi et al 2007;Goren et al 2008) in agreement with a model of a function for open chromatin. If origin definition and activation would be purely defined by chromatin, one might expect that any relief of gene repression will lead to early replication at any chromosomal position.…”
mentioning
confidence: 71%
“…Moreover, in higher eukaryotes, early replication correlates with a high probability of transcription and the presence of histone modifications characteristic of active chromatin such as histone acetylation (Schwaiger et al 2009;Hansen et al 2010). Histone hyperacetylation has been directly implicated to facilitate origin activation and thereby early replication timing (Aggarwal and Calvi 2004;Calvi et al 2007;Goren et al 2008) in agreement with a model of a function for open chromatin. If origin definition and activation would be purely defined by chromatin, one might expect that any relief of gene repression will lead to early replication at any chromosomal position.…”
mentioning
confidence: 71%
“…5). Several single-gene studies have suggested a positive function of histone acteylation for origin activity (Lin et al 2003;Aggarwal and Calvi 2004;Danis et al 2004;Calvi et al 2007;Hartl et al 2007;Goren et al 2008). Other reports, however, did not support this model (Prioleau et al 2003;Dazy et al 2006;Gregoire et al 2006).…”
Section: H4k16 Acetylation Links Chromatin With Early Replication Andmentioning
confidence: 97%
“…Transcription factors at sites of replication initiation have been shown to stimulate replication in many systems, including viruses, yeast, Drosophila, and Xenopus (8,9). This stimulation may be a consequence of direct interaction with components of the replication machinery or of facilitating the access of the replication complexes to DNA through recruitment of chromatin remodeling complexes (10)(11)(12). Here we present a high-resolution map of replication origins in HeLa cells based on hybridization of short nascent strands (SNS) on DNA microarrays covering ENCODE regions.…”
mentioning
confidence: 99%